2018
DOI: 10.20448/journal.522.2018.42.114.120
|View full text |Cite
|
Sign up to set email alerts
|

Flow Experiences in Physical Education Classes: The Role of Perceived Motivational Climate and Situational Motivation

Abstract: The purpose of this study was to determine the role of perceived motivational climate and situational motivation levels on dispositional flow in physical education classes. 242 boys (Mage=13.38; SD=0.95) and 251 girls (Mage=13.27; SD=0.88) a total of 493 secondary school students (Mage=13.32; SD=0.91) voluntarily participated in this study. Physical Education Situational Motivational Scale, Learning and Performance Orientation in Physical Education Classes Questionnaire and Physical Education Dispositional Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…Other studies, such as [48], reflect how students do better academically when there is a motivational, home-oriented climate. The learning climate created by the teacher and the student's active participation have been identified as fundamental to increase students' motivation [49]. Cooperative Learning climates, like the ones promoted in this study, can boost students' motivation in Physical Education since they have been found dependent upon three elements: cooperation, participation, and respect [50].…”
Section: Discussionmentioning
confidence: 78%
“…Other studies, such as [48], reflect how students do better academically when there is a motivational, home-oriented climate. The learning climate created by the teacher and the student's active participation have been identified as fundamental to increase students' motivation [49]. Cooperative Learning climates, like the ones promoted in this study, can boost students' motivation in Physical Education since they have been found dependent upon three elements: cooperation, participation, and respect [50].…”
Section: Discussionmentioning
confidence: 78%
“…A possible explanation for this is that male adolescents at this age are often moved to a greater extent towards the achievement of extrinsic goals, motivated by competitiveness. On the other hand, females are more likely to strive for the achievement of intrinsic rewards such as improvement and personal development [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to BPN, Alp et al [66], affirmed the relationship between the BPN and the autotelic experience in secondary school students. Regarding the perception of support for autonomy, Ada et al [19], determined that autonomy is not an element of dispositional flow, however, they also determined it as a predictive factor in PE students.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their satisfaction increases the degree of intrinsic motivation [10,11] and leads to positive consequences at a cognitive, affective and behavioural levels (consequent variables), corresponding in this study with autotelic experience and enjoyment [16] As far as the student's perception of support for autonomy is concerned, it is understood as the use of a non-controlling or non-authoritarian teaching style, which aims to form a perception of autonomy in the student, that is, that the students feel that they are responsible for their actions [17]. This perception of support for autonomy is very important in students, since the greater the perception of support for autonomy is, the higher the self-determined motivation towards an activity will be [18,19] Regarding one of the consequent variables of this study, we must highlight autotelic experience, which is described by Csikszentmihalyi [20] as an activity whose final objective is the experience itself, which is carried out not for the hope of some future benefit, but simply because the activity in itself is the reward. It constitutes one of the most representative factors of Dispositional Flow-optimal and momentary experience in which the person is absorbed in a specific activity, feeling great enjoyment-favoured by intrinsic motivation and for which the level of individual skill and the difficulty of the task are combined [20].…”
Section: Introductionmentioning
confidence: 99%